Interactive Web-Based Visualization of Multidimensional Physical and Astronomical Data - Diblen, Faruk; Hendriks, Luc; Stienen, Bob; Caron, Sascha; Bakhshi, Rena; Attema, Jisk (Frontiers in Big Data, 2021)
In this manuscript, we propose expanding the use of scientific repositories such as Zenodo and HEP data, in particular to better study multiparametric solutions of physical models. The implementation of interactive web-based visualizations enables quick and convenient re-analysis and comparisons of phenomenological data. To illustrate our point of view, we present some examples and demos for dark matter models, supersymmetry exclusions and LHC simulations.